Analisis Sumber Tafsir Juz 30 dalam Tarjuman al-Mustafid Karya Abdurrauf al-Fanshuri - Siagian, Roihatul Jannah; Ilyas Nasution, Muhammad; Irfan, Muhammad; Sormin, Nurhabibah; Lutfiah, Habibah (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
Tafsir Tarjuman al-Mustafid written by Sheikh Abdur Rauf al-Fanshuri al-Jawi, is one of the tafsirs in Jawi Arabic (Malay) which is considered the earliest and most complete tafsir in the archipelago. This article will discuss the introduction of Tarjuman al-Mustafid's book of interpretations by explaining the biography and writing of his book of interpretations. This research is bibliographic research, namely research that focuses on library research by collecting, reading and reviewing literature related to Tarjuman al-Mustafid, while the method used in this research is analytical descriptive. The results of the research, the full name of Sheikh Abdur Rauf al-Fanshuri al-Jawi, was born in Singkel around 1620 AD. Another opinion says that Sheikh Abdur Rauf was born around 1024 H/1615 AD and died in 1105 H/1693 AD. There are two The view regarding the source of writing this tafsir is firstly as a translation of Baidhawi's tafsir, secondly as a translation of the books of Jalalain and Al-Khazin. To determine the method of writing Tafsir Tarjuman al-Mustafid, we can look at it from two angles, namely the angle of interpretation and the angle of meaning. When we explore it from the perspective of a method of interpretation that explains the sequence of verses and explains the aspects and contents of the verse content, this is the tahlili method. Meanwhile, when viewed from the point of view of the meaning explained in the Tafsir, the method applied in writing the Tafsir is the ijmali method. Because the explanation is short, concise, easy to understand and suitable for beginners.